Pengaruh Penghindaran Pajak dan Risiko Pajak terhadap Biaya Utang pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of tax avoidance and tax risk on the cost of debt in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The background of the study is based on the phenomenon of fluctuations in the Effective Tax Rate (ETR) and the importance of understanding tax strategies and their risks in relation to a company's financing structure. This study uses a quantitative approach with a panel data regression method. The research sample consisted of 25 manufacturing companies selected through a purposive sampling technique. The independent variables analyzed were tax avoidance and tax risk, while the dependent variable was the cost of debt. The results show that partially, tax avoidance has no significant effect on the cost of debt, nor does tax risk have a significant effect individually. Simultaneously, tax avoidance and tax risk have a significant effect on the cost of debt. This finding implies that although neither individually has an impact, the combination of tax strategies and inherent risks can influence creditors' assessments of a company, ultimately impacting the cost of debt.